2016
DOI: 10.1051/matecconf/20167801058
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency: The Implementation of Minimum Energy Performance Standard (MEPS) Application on Home Appliances for Residential

Abstract: Abstract. Generally, Minimum Energy Performance Standard (MEPS) has been widespread across the country especially developed country. However, most consumers do not even know about the MEPS. Without sufficient knowledge, much energy have been wasted before this. The aim of this study is to review the implementation of MEPS of Asia country and to compare electricity consumption of home appliances with star rating and without star rating. In order to fulfil the objectives of the study, the equipment must be chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Ayala and Sola suggested that the EU energy efficiency (EE) label for appliances was a key instrument for driving consumers towards more energy efficient purchase [10]. While addressing the implementation of MEPS application on home appliances for residential, Rahman and associates [11] acknowledged that home appliances with MEPS in context are more efficient on energy saving compared to those without MEPS and energy labelling, while Schencking and Stamminger [12] sum up that "energy labels provides relevant information to the consumers to help them make an environmentally beneficial choice when purchasing a new appliances.…”
Section: Meps and Labellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayala and Sola suggested that the EU energy efficiency (EE) label for appliances was a key instrument for driving consumers towards more energy efficient purchase [10]. While addressing the implementation of MEPS application on home appliances for residential, Rahman and associates [11] acknowledged that home appliances with MEPS in context are more efficient on energy saving compared to those without MEPS and energy labelling, while Schencking and Stamminger [12] sum up that "energy labels provides relevant information to the consumers to help them make an environmentally beneficial choice when purchasing a new appliances.…”
Section: Meps and Labellingmentioning
confidence: 99%
“…Making productive use of mini-grids through energy efficient, high quality off-grid household appliance and productive use increase energy demand and balances load. The growth of mini-grids sector highly depends on offgrid appliance market growth which the network is complex and continues to change [11].…”
Section: Off-grid Appliancesmentioning
confidence: 99%